The effect of ultra-processed very low-energy diets on gut microbiota and metabolic outcomes in individuals with obesity: A systematic literature review. Issue 3 (May 2020) - Lane, Melissa; Howland, Gina; West, Madeline; Hockey, Meghan; Marx, Wolfgang; Loughman, Amy; O'Hely, Martin; Jacka, Felice; Rocks, Tetyana
Abstract: This systematic review investigated the effects of ultra-processed very low-energy diets on gut microbiota and metabolic outcomes in individuals with obesity. MEDLINE complete, EMBASE, Scopus, Cochrane and CINAHL were searched between date of inception and October 2019. Seven trials were reviewed (a total of 130 participants, with 10 to 44 participants in each trial). Of these, five were single-arm interventions and included very low-energy diets adjunctive to comprehensive lifestyle interventions such as nutritional counselling, behavioural therapy and exercise programmes. Changes to taxa within the Firmicutes phylum were found, including reduced abundance of potentially beneficial butyrogenic microbes ( Roseburia, Faecalbacterium prausnitzii, Lactobacillus, Bifidobacterium and Lachnospiraeceae ). Conversely, increased abundance of potentially pathogenic or opportunistic microbes from the Bacteroidetes phylum was reported, including increases in Alistipes and Bacteroides taxa. However, outcomes were inconsistent, with some trials also showing decreases in Bacteroides taxa and increases in commensal microbiota, such as Lachnospiraceae and Bifidobacteriaceae. The changes in metabolic parameters observed from baseline to after the ultra-processed very low-energy diets were mostly beneficial or were not significantly altered. Although the selected articles were deemed to have satisfactory methodological quality, to understand the possible direct effects of these regimens on gut microbiota, further rigorously designed trials, with more standardised microbiological sequencing techniques and detailed reporting, are required. Study registration: Prospero ID: CRD42019124436.